Bioluminescent Mammalian Cells Grown in Sponge Matrices to Monitor Immune Rejection - Okechukwu Ojogho; Alice Li; Craig W. Zuppan; Alan Escher (Molecular Imaging)
The growth and bioluminescence of cells seeded in collagen and gelatin sponge matrices were compared in vitro under different conditions, and immune rejection was quantified and visualized directly in situ based on loss of bioluminescence activity. Mammalian cells expressing a Renilla luciferase complementary deoxyribonucleic acid (cDNA) were used to seed collagen and gelatin sponge matrices soaked in either polylysine or gelatin to determine optimal growth conditions in vitro. The sponges were incubated in tissue culture plates for 3 weeks and received 2, 9, or 15 injections of coelenterazine. Measurements of bioluminescence activity indicated that gelatin sponges soaked in gelatin emitted the highest levels of light emission, multiple injections of coelenterazine did not affect light emission significantly, and light emission from live cells grown in sponges could be measured qualitatively but not quantitatively. Histologic analysis of sponge matrices cultured in vitro showed that cells grew best in gelatin matrices. Visualization of subcutaneously implanted sponges in mice showed accelerated loss of light emission in immunocompetent BALB/c mice compared with immunodeficient BALB/c- scid mice, which was associated with increased cell infiltration. Our results indicate that sponge matrices carrying bioluminescent mammalian cells are a valid model system to study immune rejection in situ.